Sodium cholate aggregation and chiral recognition of the probe molecule (R,S)-1,1'-binaphthyl-2,2'-diylhydrogenphosphate (BNDHP) observed by 1H and 31P NMR spectroscopy - Hebling, Christine M (Langmuir : the ACS journal of surfaces and colloids, 2008)
Bile salt micelles can be employed as a pseudostationary phase in micellar electrokinetic capillary chromatography (MEKC) separations of chiral analytes. To improve MEKC separations of chiral analytes, a molecular level understanding of micelle aggregation in the presence of analyte is needed. Here, aggregation of sodium cholate has been observed by exploiting the presence of a model analyte molecule. The 31P and 1H nuclear magnetic resonance spectroscopy (NMR) chemical shifts of (R,S)-1,1'-binaphthyl-2,2'-diylhydrogenphosphate ((R,S)-BNDHP), a model analyte in chiral MEKC separations, are demonstrated to be very sensitive to the aggregation state of the bile salt sodium cholate. In addition to probing micellar aggregation, the NMR spectral resolution of enantiomeric species is also stronglycorrelated with chiral separations in MEKC. In this work, the aggregation of sodium cholate in basic solutions (pH 12) has been observed over the concentration range 0-100 mM. The primary critical micelle concentration (cmc) was found to be 14 +/- 1 mM for basic solutions of sodium cholate. In addition, a primitive aggregate is clearly observed to form at 7 +/- 1 mM sodium cholate. The data also show pseudo-cmc behavior for secondary aggregation observed in the regime of 50-60 mM cholate. Finally, the H5-H7 edge of BNDHP is shown to be sensitive to chirally selective interactions with primary cholate micelles